Customer perception and satisfaction: eServices quality by MYSPEED to JPJ users / Ainaa Nadia Mohd Amran - Mohd Amran, Ainaa Nadia (Faculty of Business and Management, 2007)
The World Wide Web has unleashed people's imagination and a plethora of new technologies have emerged. Since these technologies have spring up to address different requirements, it has become imperative to understand how this different technology fit together.